2011
DOI: 10.1371/journal.pbio.1000590
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical Compensation of Zygotic X Transcription in Early Drosophila melanogaster Development Revealed through Single-Embryo RNA-Seq

Abstract: Mmany genes from the X chromosome are expressed at the same level in female and male embryos during early Drosophila development, prior to the establishment of MSL-mediated dosage compensation, suggesting the existence of a novel mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
396
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(425 citation statements)
references
References 57 publications
(57 reference statements)
25
396
2
2
Order By: Relevance
“…While Vielfaltig's mechanism of action is unknown, we and others previously noted an enrichment for TAGteam motifs in regions bound by six anterior-posterior transcription factors (Li et al 2008;Bradley et al 2010). Hypothesizing that this relationship between TAGteam motifs and transcription factor binding might be causative, we reanalyzed the ChIP (MacArthur et al 2009), DNase I , and RNA-seq (Lott et al 2011) data sets described above and found that the presence of TAGteam motifs is associated with high levels of binding of all assayed factors. Levels of binding are globally proportional to RNA polymerase II occupancy of promoters and gene expression levels during the onset of zygotic transcription.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 92%
See 3 more Smart Citations
“…While Vielfaltig's mechanism of action is unknown, we and others previously noted an enrichment for TAGteam motifs in regions bound by six anterior-posterior transcription factors (Li et al 2008;Bradley et al 2010). Hypothesizing that this relationship between TAGteam motifs and transcription factor binding might be causative, we reanalyzed the ChIP (MacArthur et al 2009), DNase I , and RNA-seq (Lott et al 2011) data sets described above and found that the presence of TAGteam motifs is associated with high levels of binding of all assayed factors. Levels of binding are globally proportional to RNA polymerase II occupancy of promoters and gene expression levels during the onset of zygotic transcription.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 92%
“…DNase I digestion data, measuring chromatin accessibility, is available as well for identically staged embryos Thomas et al 2011). Furthermore, a recent study measured levels of both maternally contributed and zygotically transcribed mRNAs from mitotic cycles 10-14 (Lott et al 2011) when widespread transcription of the zygotic genome commences, allowing us to connect transcription factor binding to gene expression.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
See 2 more Smart Citations
“…It is clear, therefore, that each syncytial nuclear cycle can be treated as a single, or even multiple developmental time points. A few recent RNA-sequencing (RNA-seq)-based studies have in fact divided embryonic development into time points based on syncytial nuclear divisions for this very reason (Lott et al 2011;Ali-Murthy et al 2013). In previous studies, however, the syncytial nuclear stage, especially nuclear cycles [10][11][12][13][14], have been grouped together in a small number of developmental stages or time points (Bownes 1975;Bate and Martinez Arias 1993;Graveley et al 2011).…”
mentioning
confidence: 99%